EFEKTIVITAS METODE SAND FILTER DALAM MENURUNKAN TINGKAT KEKERUHAN DAN KADAR E.COLI PADA AIR SUMUR - Bertha Mangallo; Reynom Alfontus; Agnes Dyah Novitasari Lestari (Jurnal Natural, 2023)
This study aims to determine the effectiveness of the sand filter method in reducing turbidity and e.coli levels in dug well water. The research method involved preparing filter media consisting of sand and beach pebbles, charcoal from coconut shells, pottery made from clay, and palm fiber. Water treatment is carried out using a filtration column containing filter media. The characteristics of dug well water before processing showed a turbidity level of 6.5 NTU and levels of e.coli ≥1898 CFU/100 mL. The results of the analysis of the quality of processed water using the sand filter method show that the effectiveness of the sand filter method in reducing turbidity levels reaches 100% while reducing e.coli levels reaches 95%.